Extracorporeal organ support and the kidney - Muciño-Bermejo, Maria-Jimena (Frontiers in Nephrology, 2022)
The term extracorporeal organ support (ECOS) includes all forms of extracorporeal organ support, encompassing kidney, respiratory, cardiac and liver support. In an era of increasing incidence and survival of patients with single or multiple organ failure, knowledge on both multiorganic crosstalk and native organ-extracorporeal support interactions have become increasingly important. Immerse within the cross-talk of multiple organ failure (MOF), Acute kidney injury (AKI) may be a part of the clinical presentation in patients undergoing ECOS, either as a concurrent clinical issue since the very start of ECOS or as a de novo event at any point in the clinical course. At any point during the clinical course of a patient with single or multiple organ failure undergoing ECOS, renal function may improve or deteriorate, as a result of the interaction of multiple factors, including multiorganic crosstalk and or native organ/ECOS interactions. Besides multiorgan crosstalk during MOF, the main common physiopathological ways in which ECOS may influence renal function includes: 1)Hemodynamic changes, 2)Neurohumoral changes, 3)Cytokine profile switch, 4)ECOS-associated coagulation abnormalities, 5)Toxin/drugs clearance and 6) Circuit-related factors. The main aim of this review is to summarize the described mechanisms influencing the renal function during the course of ECOS, including hemodialysis, hemofiltration, venovenous extracorporeal membrane oxygenation, venoarterial extracorporeal membrane oxygenation, extracorporeal carbon dioxide removal and albumin dialysis.